Proposal for Exchange Text message Based on Image - Mohammed, R. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The messages are ancient method to exchange information between peoples. It had many ways to send it with some security.    Encryption and steganography was oldest ways to message security, but there are still many problems in key generation, key distribution, suitable cover image and others. In this paper we present proposed algorithm to exchange security message without any encryption, or image as cover to hidden. Our proposed algorithm depends on two copies of the same collection images set (CIS), one in sender side and other in receiver side which always exchange message between them.      To send any message text the sender converts message to ASCII code. Chose one image from its (CIS) .Locate for each ASCII code in red or green or blue band color of chosen image. Store(x,y) location and color of correspond value. After that draw lines in graphic line image (GLI) by using this (x,y) and S (letter sequence) and color with white background.Then send the graphic lines image (GLI) with serial number of chosen image from (CIS) to receiver. After receiving the (GLI) in other side, the receiver will choose image from its (CIS) according to serial number which it received then doing some steps to display the extract message.